Drop Size Distribution Characteristics of Seven Typhoons in China. Issue 12 (19th June 2018) - Wen, Long; Zhao, Kun; Chen, Gang; Wang, Mingjun; Zhou, Bowen; Huang, Hao; Hu, Dongming; Lee, Wen‐Chau; Hu, Hanfeng
Abstract: This study is the first attempt to investigate the characteristics of the drop size distribution (DSD) and drop shape relation (DSR) of seven typhoons after making landfall in China. Four typhoons were sampled by a C‐band polarimetric radar (CPOL) and a two‐dimensional video disdrometer (2DVD) in Jiangsu Province (East China) while three typhoons were sampled by two 2DVDs in Guangdong Province (south China). Although the DSD and DSR are different in individual typhoons, the computed DSD parameters in these two groups of typhoons possess similar characteristics. The DSR is more spherical, and the shape‐slope ( μ‐ Λ) relation has a significantly lower value of μ for a given Λ than that in typhoons in the Taiwan area, indicating different microphysical processes of typhoons between continental China and other regions (western Pacific and Atlantic). The convective precipitation of typhoons contains higher raindrop concentration and lower raindrop diameter than that of the maritime convection. A Z (reflectivity factor)‐ R (rain rate) relationship, Z  = 147.28 R 1.38, is derived for typhoons over land in China. The contoured frequency by altitude diagrams of CPOL polarimeteric parameters and the vertical distributions of hydrometeors and retrieved DSD parameters are further investigated to better reveal the microphysical processes of two typhoons (Matmo and Soudelor). Despite the differences in DSDs and polarimetric parameters, microphysical characteristics in both typhoons are similar. The CPOL‐derived microphysical properties, in conjunction with high freezing level, suggest that warm rain accretion processes dominate typhoon rainfall after landfall in China. Key Points: Raindrops of typhoons in continental China are smaller and more spherical with higher concentration than that of the Pacific and Atlantic More accurate precipitation estimation, raindrop size distribution, and polarimetric radar parameters are obtained for typhoon rainfall Warm rain processes dominate the formation and evolution of typhoon rainfall in continental China